2022
DOI: 10.1136/bmj-2022-070102
|View full text |Cite
|
Sign up to set email alerts
|

Change in covid-19 risk over time following vaccination with CoronaVac: test negative case-control study

Abstract: Objective To estimate the change in odds of covid-19 over time following primary series completion of the inactivated whole virus vaccine CoronaVac (Sinovac Biotech) in São Paulo State, Brazil. Design Test negative case-control study. Setting Community testing for covid-19 in São Paulo State, Brazil. Participants Adults aged ≥18 years who were residents of São Pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Studies designed to identify and mitigate such biases should be prioritized to estimate the extent and timescale of waning effectiveness. 15,33 We observed "negative" VE for some vaccination groups of homologous booster particularly for the Omicron period and homologous booster against symptomatic Covid-19. This phenomenon has been observed in some VE studies against Covid-19 and it is likely related to uncontrolled bias.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Studies designed to identify and mitigate such biases should be prioritized to estimate the extent and timescale of waning effectiveness. 15,33 We observed "negative" VE for some vaccination groups of homologous booster particularly for the Omicron period and homologous booster against symptomatic Covid-19. This phenomenon has been observed in some VE studies against Covid-19 and it is likely related to uncontrolled bias.…”
Section: Discussionmentioning
confidence: 85%
“…Studies designed to identify and mitigate such biases should be prioritized to estimate the extent and timescale of waning effectiveness. 15,33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For mRNA vaccines, the waning of effectiveness against hospitalization during the Omicron wave was seen 3–4 months after two doses of vaccine (decreasing from a peak of 80.3% to 56.3%) and after the third dose of vaccine (from 81.6% to 50.0%) [ 18 ]. In one study [ 19 ], after the second dose of inactivated virus vaccine, the odds ratio of having symptomatic COVID-19 increased with time across age groups. Between 0–13 days and >180 days, the odds in 18–39-year-olds were 1.41 to 1.67, but they were 1.22 to 1.65 in those > 80 years old.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the confidence intervals for ORs with 1, 2, 3 doses were overlapping, indicating the estimates of ORs by doses were not significantly different statistically. Other studies reported that after two doses of inactivated vaccines, the risk of hospitalization or death after being infected with SARS-CoV-2 virus increased gradually compared with being recently vaccinated ( 32 ), and nearly doubled by 6 months after vaccination ( 33 ). Statistical analyses have shown that the relative effectiveness of booster vaccination with BNT162b2 (Pfizer/BioNTech) or mRNA-1,273 (Moderna) following primary vaccination with ChAdOx1-S (AstraZeneca) or BNT162b2 ranged from 85 to 95% ( 34 ).…”
Section: Discussionmentioning
confidence: 99%